2003
DOI: 10.1046/j.1365-2249.2003.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immune parameters and their correction in human cases of tick-borne encephalitis

Abstract: SUMMARY Tick-Borne Encephalitis virus (TBEV) causes dangerous central nervous system diseases in humans.General infection leads to the development of meningitis or encephalitis, which is characterized by swelling of the brain due to inflammation. Tetracyclines may act locally to moderate inflammation in the CNS. In this study, we investigated the potential clinical benefits of administering tetracycline hydrochloride to patients hospitalized due to suspected TBEV infection presenting with fever and evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 36 publications
4
52
0
4
Order By: Relevance
“…In general, the case fatality rate is approximately 1-2 % following European subtype infection, but can be as high as 20-40 % following infection with a far-eastern subtype (Mandl, 2005). Infection with the Siberian subtype produces a mortality rate of no more than 2-3 % (Atrasheuskaya et al, 2003). However, it is possible that the high mortality figures for the far-eastern subtype may be due to the lack of detection of mild cases.…”
Section: Clinical Manifestationsmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, the case fatality rate is approximately 1-2 % following European subtype infection, but can be as high as 20-40 % following infection with a far-eastern subtype (Mandl, 2005). Infection with the Siberian subtype produces a mortality rate of no more than 2-3 % (Atrasheuskaya et al, 2003). However, it is possible that the high mortality figures for the far-eastern subtype may be due to the lack of detection of mild cases.…”
Section: Clinical Manifestationsmentioning
confidence: 90%
“…Recently, a number of studies have investigated the level of certain cytokines and chemokines in the serum and CSF of patients with TBE. A study in Russia found that on admission to hospital, TBE patients had elevated serum levels of tumour necrosis factor (TNF)-a, interleukin (IL)-1a and IL-6, where IL-1a and TNF-a were acting synergistically to initiate the cascade of inflammatory mediators by targeting the endothelium; levels of these cytokines then declined during the first week of hospitalization, which was accompanied by an increase in levels of IL-10 (an inhibitor of cytokine synthesis) (Atrasheuskaya et al, 2003). Another study found that during TBEV infection, the concentration of CXCL10 was higher in CSF than in serum, suggesting a role in the recruitment of CXCR3-expressing T cells into the CSF (Lepej et al, 2007).…”
Section: Host Immune Responsementioning
confidence: 99%
“…The later presents as meningitis, meningoencephalitis or meningoencephalomyelitis of different severity, from self-limited to life-threatening [1,2]. Reasons of this clinical diversity are not fully understood, but host-related factors, including genetically determined variability of the inflammatory/immune response, are likely to play an important role [3][4][5][6][7]. The outcome of a neurotropic Flavivirus infection is decided at several stages, including (1) the initial response at the entry site; (2) the extent of the peripheral infection and related inflammation; (3) the penetration into cns (neuroinvasiveness); (4) the potential to cause neuronal damage (neurovirulence), with complex interactions between the virus and the host response at each of these steps [8][9][10].…”
Section: Introductionmentioning
confidence: 94%
“…10.001 1043-4666/Ó 2014 Elsevier Ltd. All rights reserved. [3,13,17,18]. Type I interferons (including IFNa and IFNb) are involved in anti-viral defense and up-regulated by the recognition of viral molecular patterns, including binding of a double-stranded RNA by Toll-like receptor 3 (TLR3).…”
Section: Introductionmentioning
confidence: 99%
“…Both can pose a diagnostic and therapeutic challenge for practicing neurologists since no test is definitively specific for LNB, and many TBE symptoms mimic those of several other central nervous system (CNS) diseases [11,12] . TBE leads to the development of meningitis or encephalitis, which is characterized by swelling of the brain due to inflammation [13] . Although TBE is most commonly recognized as a neurologic disease, mild febrile illnesses can also occur and long-lasting or permanent neuropsychiatric sequelae are observed in 10-20% of infected patients.…”
mentioning
confidence: 99%